Fatigue and vigilance in medical experts detecting breast cancer - Sian Taylor‐Phillips; David Jenkinson; Chris Stinton; Melina A. Kunar; Derrick G. Watson; Karoline Freeman; Alice Mansbridge; Matthew Wallis; Olive Kearins; Sue Hudson; Aileen Clarke (2024)
An abundance of laboratory-based experiments has described a vigilance decrement of reducing accuracy to detect targets with time on task, but there are few real-world studies, none of which have previously controlled the environment to control for bias. We describe accuracy in clinical practice for 360 experts who examined >1 million women’s mammograms for signs of cancer, whilst controlling for potential biases. The vigilance decrement pattern was not observed. Instead, test accuracy improved over time, through a reduction in false alarms and an increase in speed, with no significant change in sensitivity. The multiple-decision model explains why experts miss targets in low prevalence settings through a change in decision threshold and search quit threshold and propose it should be adapted to explain these observed patterns of accuracy with time on task. What is typically thought of as standard and robust research findings in controlled laboratory settings may not directly apply to real-world environments and instead large, controlled studies in relevant environments are needed.